Efeito das células derivadas da medula óssea no tratamento da insuficiência renal crônica experimental - Caldas, Heloisa Cristina (2011)
Chronic renal failure (CRF) is characterized by progressive and irreversible loss of renal function and its treatment generates significant public spending for maintenance and care of patients on dialysis. Stem cell (SC) therapy, in its potential for treatment of chronic diseases, may be a promising strategy for repairing the damage from or slowing the progression of CRF. There are questions about cell type, quantity of cells, method and ideal place for deployment of SC and the role it plays in the repair of renal parenchyma. Objective: 1) To evaluate the effect of infusion of bone marrow derived cells (BMDC) in the treatment of experimental CRF; 2) Evaluate the combined effect of SC and biomaterial (BM) in the progression of CRF and study the effect of this therapy in different stages of CRF; 3) Evaluate the development of techniques for isolation and cultivation of human umbilical cord blood (HUCB) mesenchymal cells Methods: Article 1: We used the 5/6 mass reduction model to induce experimental CRF. Kidney function was measured at the beginning of the experiment and 60 and 120 days after the surgery; Article 2: Animals were subdivided as to the amount of renal parenchyma injured (5/6 or 2/3), the use of BM as a scaffold to cell implantation, and cell type used (mononuclear or mesenchymal cells). Renal function was evaluated on days 0, 45, and 90 after surgery. Histological and immunohistochemical analyses were done in all groups at the end of the study; Article 3: Ten samples of HUCB were used and two different procedures for cultivation of mesenchymal stem cells (MSC) were tested: without Ficoll-Paque density gradient, to obtain nucleated cells; with Ficoll-Paque density gradient, for obtaining mononuclear cells. Results: Article 1: CRF progression analysis showed that treatment with BMDC significantly reduced the rate of decline of creatinine clearance (Clcr) when compared with the control group; Article 2:Treated animals showed significantly lower increases in serum creatinine and 24 hour proteinuria, and higher increases in Clcr after 90 days when compared to control animals in both models of CRF; Article 3: The MSC in culture from the method without Ficoll-Paque density gradient maintained growth forming confluent cell foci. Conclusions: Article 1: Progression of CRF can be delayed by injection of BMDC in the renal parenchyma; Article 2: a) Use of SC combined with BM can be an alternative way to administer BMDC; b) Cell therapy seems to be most effective when administered in less severe stages of CRF; Article 3: Nucleated cells without using Ficoll-Paque density gradient showed more efficiency in the cultivation of MSC from HUCB when compared with the procedure employing Ficoll-Paque density gradient.